NAB2-STAT6 Gene Fusion in Meningeal Hemangiopericytoma and Solitary Fibrous Tumor - Fritchie, Karen J.; Jin, Long; Rubin, Brian P.; Burger, Peter C.; Jenkins, Sarah M.; Barthelmeß, Sarah; Moskalev, Evgeny; Haller, Florian; Oliveira, Andre M.; Giannini, Caterina (Journal of Neuropathology and Experimental Neurology, 2016)
Meningeal solitary fibrous tumor (SFT) and hemangiopericytoma (HPC) are considered to be distinct entities in the WHO Classification of CNS Tumours (2007). They harbor NAB2-STAT6 fusions similar to their soft tissue counterparts, supporting the view that they are part of a tumor continuum. We examined 30 meningeal-based tumors originally diagnosed as either SFT or HPC. These showed a spectrum of morphologic features and were diagnosed as SFTs, malignant SFTs, HPCs, or tumors with "intermediate" features. All of the tumors showed nuclear expression of STAT6. SFTs consistently expressed diffuse CD34, while HPCs and intermediate tumors had heterogeneous staining. NAB2-STAT6 fusions were identified in 20 cases, including 7 with exon 4-exon 3, 9 with exon 6-exon 17, and 4 with exon 6-exon 18 fusions. NAB2 exon 4-STAT6 exon 3 fusion correlated with classic SFT morphology and older age and showed a trend toward less mitotic activity; there was also a trend toward more aggressive behavior in tumors lacking NAB2 exon 4-STAT6 exon 3. Thus, despite their clinical and morphologic differences, meningeal-based SFTs, HPCs, and tumors with intermediate features, similar to their soft tissue counterparts, form a histopathologic spectrum unified by STAT6 immunoexpression and NAB2-STAT6 fusion.
EVALuna2:6771